Architectural and structural type of self-propelled tethered underwater vehicles with improved maneuverability - Blintsov, Oleksandr (КНУБА, 2016)
The modern underwater complexes with umbilical tethers development trends overview and their underwater vehicles as technological equipment carriers peculiarities are given. The main disturbances that influence an underwater vehicle motion within underwater complex with umbilical tethers and the quality of work that it performs are described. The constructive elements layout basic concept of an underwater vehicle as a part of an underwater complex with umbilical tethers is analyzed. The propulsive complexes typical configurations are overviewed.The underwater vehicle progressive and rotary spatial motions separation concept is proposed. The concept makes it possible to design underwater vehicles with minimal disturbances influence while moving or positioning at six degrees of freedom and thus provide control quality enhancement of technological equipment installed on an underwater vehicle.The theoretical basis of a new architectural and-structural type of a self-propelled tethered underwater vehicle consisting of rotary and progressive motion platforms is developed.The possible self-propelled tethered underwater vehicle design of the new architectural-and structural type consisting of three propulsive devices and three rotary drives for processing equipment six freedom degrees motion is proposed.
Keywords: underwater vehicle; Architectural and-structural type.